A pilot study on the challenges to sustain the authenticity of the Malay heritage food, dodol, in the southern states of Malaysia - Ismail, Norsyahidah; Ab. Karim, Muhammad Shahrim; Ishak, Farah Adibah Che; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2023)
This research is a pilot study using qualitative method with phenomenological case study approach. Its objective is to explore the challenges of sustaining dodol among entrepreneurs in the southern states of Malaysia. In-depth, face-to-face semi-structured interviews were conducted on three informants who are also dodol entrepreneurs. There are two research questions in this study. The first research question is “How do the entrepreneurs preserve dodol?” in which three subthemes have emerged i.e., (i) maintaining the use of natural ingredients of dodol, (ii) using traditional tips or petua in the process of making dodol and (iii) maintaining traditional skills in the process of making dodol. The second research question is “What are the challenges faced by their businesses to sustain dodol?” in which four themes have emerged i.e., (i) the preservation of dodol’s authentic taste, (ii) the financial challenges in maintaining the business, (iii) the lack of quality ingredients and sources to produce dodol and (iv) the lack of workforce in the process of cooking dodol. The findings of this pilot study revealed the current challenges to sustain dodol business and to preserve dodol as a Malay traditional or heritage food.